2021
DOI: 10.1136/jech-2020-215716
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and birth outcomes in the ELSPAC pregnancy cohort

Abstract: ObjectivesThe aim of this study was to identify dietary patterns in a Czech pregnancy cohort established in the early postcommunist era and investigate associations between dietary patterns, maternal characteristics and birth outcomes.MethodsPregnant women were recruited for the Czech part of the European Longitudinal Study of Pregnancy and Childhood. A self-reported questionnaire answered in late pregnancy was used to assess information about the weekly intake of 43 food items. Information about birth outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
2
5
1
Order By: Relevance
“…Two articles explored depressive symptoms during pregnancy [ 46 , 88 ]. Neonatal outcomes included LBW, investigated in eleven articles [ 21 , 40 , 43 , 44 , 47 , 48 , 53 , 65 , 73 , 80 , 86 ]; LGA, investigated in eight articles [ 47 , 50 , 54 , 66 , 68 , 73 , 82 , 87 ]; birth length, explored in four articles [ 48 , 54 , 60 , 86 ]; one publication reporting body mass index (BMI)/age at birth [ 59 ]; five reporting preterm birth [ 22 , 48 , 55 , 83 , 85 ]; and offspring congenital heart defects, examined in two publications [ 70 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles explored depressive symptoms during pregnancy [ 46 , 88 ]. Neonatal outcomes included LBW, investigated in eleven articles [ 21 , 40 , 43 , 44 , 47 , 48 , 53 , 65 , 73 , 80 , 86 ]; LGA, investigated in eight articles [ 47 , 50 , 54 , 66 , 68 , 73 , 82 , 87 ]; birth length, explored in four articles [ 48 , 54 , 60 , 86 ]; one publication reporting body mass index (BMI)/age at birth [ 59 ]; five reporting preterm birth [ 22 , 48 , 55 , 83 , 85 ]; and offspring congenital heart defects, examined in two publications [ 70 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Teixeira et al [ 60 ] observed that women who consumed more “snacks, sandwiches, sweets and soft drinks” were significantly more likely to deliver SGA (birth weight and birth length <10th percentile) babies (RR: 1.92; 95% CI: 1.08, 3.39). Mikes et al [ 86 ] showed that higher consumption of unhealthy foods (confectionary, fried, and processed meats) was associated with lower birth length: (β = −0.10 cm; 95% CI: −0.19, −0.01). One study explored BMI-for-age z score at birth and reported a decrease of 20.41 standard deviations (SD) (95% CI: 20.79, 20.03) associated with a diet characterized by a high intake of white bread, red and processed meat, French fries, fried chicken, and vitamin C–rich drinks [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall findings suggest that pregnant women, regardless of geographical locations, tend to make consistent food choices (either sufficient or insufficient intake). Considering the adverse health consequences of inadequate dietary intake for mothers and their offspring [ 19 , 20 ], antenatal nutrition counseling together with dietary monitoring and education services should be provided to pregnant women, particularly for those who show signs of inadequate dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) attempted to evaluate the average exposure to acrylamide in foods, however, this is difficult to measure with traditional instruments available in nutritional research [ 5 ]. At the same time, increasing research is reporting that higher dietary acrylamide intake could be associated with a higher risk of cancer, in particular genito-urinary [ 6 , 7 ] or negative outcomes in pregnancy and in newborns [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%